(untitled) (Annals of Medical Research, 2021)
Aim: When we want to determine the difference in leg height by using only scoliosis radiographs in patients with scoliosis; we have looked for answer to the question of where should be the accurate measurement point for values that are closest to reality.Material and Methods: In this study 129 patients of our hospital between December 2016and 2018 with scoliosis radiography and leg height graphies were detected. The actual leg height difference was calculated on leg height graphies. Afterwards, the right and left femoral head top points were determined on scoliosis graphy. A parallel line was drawn from the top of the right femoral head. By measuring the distance of this line to the top point of left femur; difference between right and left legs was calculated. The same procedure was repeated after determining the right and left acetabulum top points and right and left iliac wing top points Results: A total of 129 patients, including 45 male and 84 female patients, were evaluated. Significant results were obtained from the correlation analysis between the leg length difference of the total patients and the distance between the acetabulum (p0,0001).Statistically significant correlation was found between iliac wing distance and femur length difference measurements (p0,0001).A significant correlation was detected between Femur head top spot difference measurements and length differences that were measured with orthoroentgenogram (p0,0001). Conclusion: The difference between the top point of the femoral head, the acetabulum or the iliac wing can be used on scoliosis graphy which was taken during the follow-up of leg length discrepancy in scoliosis patients.Keywords: Scoliosis; limb length discrepancy; radiography; osteogenesis.